Chemical Composition and Clinical Potential of Shrubby Cinquefoil (Pentaphylloides fruticosa (L.) O. Schwarz) Shoots: A Review - A. V. Trebukhov; L. G. Dvornikova; M. V. Goryacheva; T. S. Maloletkina (Регуляторные исследования и экспертиза лекарственных средств, 2024)
INTRODUCTION. It is important to  study  medicinal  plants  that  are  not  listed  in the State Pharmacopoeia of the Russian Federation but are used in traditional medicine and represent an abundant source of raw materials.AIM. This study aimed to collate data on the composition and pharmacology of the biologically active substances contained in shrubby cinquefoil (Pentaphylloides fruticosa (L.) O. Schwarz).DISCUSSION. According to the reviewed literature, the underground and aboveground parts of P. fruticosa contain flavonoids, tannins, phenolic acids, triterpenoid saponins, and other compounds with significant therapeutic potential, which show antimicrobial, anti-inflammatory, and immunomodulatory properties. Most pharmacology studies of P. fruticosa bioactive metabolites investigate the modulating action they exert on innate and adaptive immune responses via various mechanisms. The majority of studies use different techniques and focus on the properties of crude extracts from morphologically different parts of the plant, which precludes meaningful comparisons of the results obtained in these studies.CONCLUSIONS. P. fruticosa is a promising medicinal plant for inclusion in the pharmacopoeia. The plant has clinical potential as an antioxidant and an immunomodulator for the prevention and treatment of many diseases. The standardisation of Р. fruticosa herbal drugs requires thorough studies. The chemical composition of various plant tissues should be analysed with due consideration of seasonal, climatic, and anthropogenic factors.